Reparative Justice and State Responsibility: Reactualizing the Due Diligence Principle in Ensuring Civil Remedies for Human Rights Violations: Reparative Justice and State Responsibility: Reactualizing the Due Diligence Principle in Ensuring Civil Remedies for Human Rights Violations - Simon S. Condro Kitono; Dedy Ardian Prasetyo; Supaphorn Akkapin (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2026)
The right to civil redress is a central pillar of reparative justice for victims of human rights violations. Although international legal instruments, such as the United Nations Basic Principles on the Right to Remedies and Reparation, affirm states’ obligation to guarantee this right, many have failed to establish mechanisms that are effective and accessible to victims. This article conceptualizes the principle of due diligence as a binding international legal standard that obliges states to prevent and respond to human rights violations and ensure the availability of accessible and enforceable civil restitution. Employing a normative legal method and a comparative case study of Argentina, Germany, and Indonesia, the analysis demonstrates that civil restitution remains the most fragile dimension of state accountability frameworks, with reparations frequently regarded as discretionary policies rather than legal mandates. To address this gap, this study advances a set of normative indicators for assessing states’ compliance with their reparation obligations. The findings highlight the imperative of embedding the principle of due diligence within national legal systems as a concrete legal obligation, thereby advancing victim-centered justice.